Working through the crisis : jobs and policies in developing countries during the great recession - Banerji, Arup (Directions in development (Washington, D.C.). Human development., 2013)
"This book looks back both at how the Great Recession affected employment outcomes in developing countries and at how governments responded. The chapters bring together a unique compilation of data and analysis from very different sources, including an inventory of policies implemented during the crisis among countries in Latin America, Eastern Europe, Asia and Africa. The overall story is that the impacts of the crisis varied considerably. The effect depended on the size of the original shock, the channels through which it was manifested, the structure of institutions in the country -- especially labor institutions -- and the specific policy responses undertaken by countries in response to the shock. While these factors led outcomes to differ across the countries studied, a few common patterns emerged. In terms of impacts, overall adjustments involved reductions in earnings growth rather than employment growth, although the quality of employment was also affected. Youth were doubly affected, being more likely to both experience unemployment and reduced wages. Men seemed to have been more strongly affected than women. In most countries where data are available, there were no major differences between skilled and unskilled workers or those living in urban or rural areas. In terms of policy responses, this crisis was characterized by a high prevalence of active interventions in the labor market and the expansion of income protection systems, as well as countercyclical stimulus. Countercyclical stimulus measures in a number of countries, when timed well and sufficiently large to mitigate the shock, were effective in reducing adverse employment effects. Specific sectoral stimulus policies also had positive effects when well-targeted. But social protection and labor market policy responses were often ad-hoc and not in line with the types of adjustments that were taking place. As a result, these policies and programs did not necessarily reach those who needed them the most and typically were biased toward formal sector workers. In retrospect, there is a sense that developing countries were not well prepared to deal with the effects of the Great Recession, suggesting room for important reforms to social protection and labor policies moving forward"--